Perawatan Kapal Nelayan Material Fiberglass di Kota Padang - Sanny Ardhy; Haznam Putra (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
Fishing boats of fiberglass materials require special care to make the vessel more durable. In the field, often found paint coating ships that have faded and peeling within a few years. Yet it is expected that the vessel can last long to continue to maximize the catch of fishermen. Most of the treatments found on fiberglass boats are light treatments, such as cracks. Cracks from gelcoat and scratches due to impact are maintenance work performed at boat or boat building. The key to fiberglass treatment is how to keep the gelcoat layer of fiber shiny. As is known, layer gelcoat is a very strong layer. But over time, weather changes and exposure to sunlight, this gelcoat layer can fade if not treated properly. In order to avoid these conditions, the most efficient way to do that is coated fiberglass with wax or special polish. Selection of care products for fiber boats also cannot be perfunctory. Certain types of waxes that have anti-ultraviolet rays are highly recommended for treatment. By doing proper maintenance techniques, will make the life of the fiber boat more durable and still look shiny.